2017
DOI: 10.2147/copd.s140901
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological incidence in pneumonia patients with pulmonary emphysema: a bacterial floral analysis using the 16S ribosomal RNA gene in bronchoalveolar lavage fluid

Abstract: Pulmonary emphysema is an important radiological finding in chronic obstructive pulmonary disease patients, but bacteriological differences in pneumonia patients according to the severity of emphysematous changes have not been reported. Therefore, we evaluated the bacteriological incidence in the bronchoalveolar lavage fluid (BALF) of pneumonia patients using cultivation and a culture-independent molecular method. Japanese patients with community-acquired pneumonia (83) and healthcare-associated pneumonia (94)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
0
19
1
Order By: Relevance
“…Berenson et al reported that the severity of COPD (FEV 1% predicted) correlated with impaired LM phagocytosis for nontypeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis [ 28 ]. Moreover, studies using clone library analysis of the 16 s RNA gene sequence have reported that H. influenzae and M. catarrhalis were more frequently identified as causative bacteria for pneumonia and/or exacerbations of COPD as well as disease progression [ 29 ]. Similarly, Streptococcus pneumoniae , which also causes acute COPD exacerbations, had been associated with the progression of emphysema possibly by inducing LMs to produce MMP-12 [ 30 ].…”
Section: Lms and Bacterial Colonization Of Copd Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Berenson et al reported that the severity of COPD (FEV 1% predicted) correlated with impaired LM phagocytosis for nontypeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis [ 28 ]. Moreover, studies using clone library analysis of the 16 s RNA gene sequence have reported that H. influenzae and M. catarrhalis were more frequently identified as causative bacteria for pneumonia and/or exacerbations of COPD as well as disease progression [ 29 ]. Similarly, Streptococcus pneumoniae , which also causes acute COPD exacerbations, had been associated with the progression of emphysema possibly by inducing LMs to produce MMP-12 [ 30 ].…”
Section: Lms and Bacterial Colonization Of Copd Airwaysmentioning
confidence: 99%
“…Therefore, the defective phagocytic and efferocytic functions of LMs in COPD could contribute to the colonization of the airways with various bacteria, specifically those known to cause acute exacerbations and pneumonia during COPD. Consequently, these infections have been related to the progression of COPD [ 29 ].…”
Section: Lms and Bacterial Colonization Of Copd Airwaysmentioning
confidence: 99%
“…People with structural lung abnormalities, such as cystic fibrosis, bronchiectasis, DPB, idiopathic pulmonary fibrosis, and emphysema, have a high incidence of P. aeruginosa airway tract colonization or infection (Poletti et al, 2006;Yamazaki et al, 2016;Naito et al, 2017;Kadowaki et al, 2015;Arancibia et al, 2002). In the present study, three participants in the PA group had DPB and 10 had radiological findings of bronchiolitis, which may reflect P. aeruginosa colonization of their bronchioles, and all participants in the PA group had structural lung abnormalities.…”
Section: Discussionmentioning
confidence: 47%
“…Previous chest CT scans were reviewed retrospectively and evaluated. In order to evaluate structural lung abnormalities related to P. aeruginosa infection, the following radiological patterns were sought: bronchiolitis (small nodules <5 mm in diameter, arranged in a centrilobular fashion), bronchiectasis (1.5 times as wide as a nearby vessel and a lack of bronchial tapering on sequential slices), traction bronchiectasis, and emphysema (Poletti et al, 2006;Yamazaki et al, 2016;Naito et al, 2017;Kadowaki et al, 2015).…”
Section: Radiological Examinationmentioning
confidence: 99%
“…of <35%, systemic steroid use, and antibiotic therapy within the preceding 3 months increased the risk of P. aeruginosa colonization [13,23,24]. The detection rates of H. influenza and P. aeruginosa were reported not to be associated with the severity of emphysematous changes [26,27]. However, chronic P. aeruginosa infection was recently reported to be associated with severe obstruction in COPD patients [28].…”
Section: Progression Of Copd and P Aeruginosamentioning
confidence: 99%